130k views
0 votes
Simplify4x2 + 12x - 162x + 106x + 24x2 + 9x + 20(2 points).O X-13(x+4)O (x-1)(x+4)3O 3(x-1)X+4O3(x - 1)(x+4)

Simplify4x2 + 12x - 162x + 106x + 24x2 + 9x + 20(2 points).O X-13(x+4)O (x-1)(x+4)3O-example-1

1 Answer

2 votes

Given equation:


((4x^2+12x-16)/(2x+10))/((6x+24)/(x^2+9x+20))

let us now simplify,


\begin{gathered} ((4x^2+12x-16)/(2x+10))/((6x+24)/(x^2+9x+20)) \\ =((4x^2+12x-16)(x^2+9x+20))/((2x+10)(6x+24)) \\ =(4(x^2+3x-4)(x^2+9x+20))/(12(x+5)(x+4)) \\ =\frac{\mleft(x^2+3x-4\mright)(x^2+9x+20)_{}}{3(x+5)(x+4)} \\ =((x+4)^2(x-1)(x+5))/(3(x+5)(x+4)) \\ =((x+4)(x-1))/(3) \end{gathered}

the answer is option 2.

User Acenturyandabit
by
4.5k points